The miracles of Saint James : translations from the Liber sancti Jacobi - Coffey, Thomas F.; Davidson, Linda Kay; Dunn, Maryjane (Italica Press, 1996)
"The twenty-two miracles associated with St. James from Book II of the Codex Calixtinus are presented here in English translation ... The Veneranda dies sermon, the seventeenth chapter of Book I of the Codex Calixtinus, is also included."--Page 4 of cover